The double-edged sword : the impact of religion on the intensity of political conflict - Pearce, Susanna Elizabeth (Trinity College (Dublin, Ireland). Department of Political Science, 2005)
The seemingly increasing frequency and deadliness of what are often termed religious conflicts have led to a revival of studies attempting to explain the relationship between religion and violence. These studies are generally case studies of a particular conflict or specific person and have not led to the development of a widely accepted theory of religious conflict. This study attempts to address the deficiency in the literature by developing and testing a model using a large number of cases that are simultaneously compared.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin